The transmission dynamics and diversity of human metapneumovirus in Peru. Issue 4 (30th March 2018) - Pollett, Simon; Trovão, Nidia S.; Tan, Yi; Eden, John‐Sebastian; Halpin, Rebecca A.; Bera, Jayati; Das, Suman R.; Wentworth, David; Ocaña, Victor; Mendocilla, Silvia M.; Álvarez, Carlos; Calisto, Maria E.; et al.
Abstract : Background: The transmission dynamics of human metapneumovirus (HMPV) in tropical countries remain unclear. Further understanding of the genetic diversity of the virus could aid in HMPV vaccine design and improve our understanding of respiratory virus transmission dynamics in low‐ and middle‐income countries. Materials & Methods: We examined the evolution of HMPV in Peru through phylogenetic analysis of 61 full genome HMPV sequences collected in three ecologically diverse regions of Peru (Lima, Piura, and Iquitos) during 2008‐2012, comprising the largest data set of HMPV whole genomes sequenced from any tropical country to date. Results: We revealed extensive genetic diversity generated by frequent viral introductions, with little evidence of local persistence. While considerable viral traffic between non‐Peruvian countries and Peru was observed, HMPV epidemics in Peruvian locales were more frequently epidemiologically linked with other sites within Peru. We showed that Iquitos experienced greater HMPV traffic than the similar sized city of Piura by both Bayesian and maximum likelihood methods. Conclusions: There is extensive HMPV genetic diversity even within smaller and relatively less connected cities of Peru and this virus is spatially fluid. Greater diversity of HMPV in Iquitos compared to Piura may relate to higher volumes of human movement, including air traffic to this location.